The Kontribusi Model Pentahelix dalam Penyebarluasan Informasi Desa Wisata Melung Kabupaten Banyumas - Asriandhini, Bunga; Lestari, Annisa Try; Nurcandrani, Prita Suci; Sari, Rida Purnama; Wiguna, King Anugrah (Kinesik, 2024)
The dissemination of information is crucial for the development of Melung Tourism Village. The current information regarding attractions, facilities, and services in Melung Tourism Village has not effectively reached the broader community. The Penta helix model represents the stakeholders responsible for this dissemination process. The Penta helix components in this study include the Government, Businesses, the Community, Academia, and the Media. This study aims to explore the contributions of these stakeholders to the information dissemination process in Melung Tourism Village. A qualitative research approach was adopted, utilizing Robert Edward Freeman's stakeholder theory to analyze the contributions of the Penta helix elements. Additionally, the interactional communication model was employed to identify the challenges faced by the Penta helix stakeholders in disseminating information about Melung Tourism Village. The findings indicate that the contributions of the Penta helix in disseminating information about Melung Tourism Village remain suboptimal, primarily due to challenges such as a lack of skilled human resources, unclear task distribution, and insufficient content updates.